Information Support of Small Business: Perspectives of Libraries on Implementation of the National Projects - Krymskaya, A. S. (Scientific and technical information processing, 2025)
This paper discusses libraries’ participation in the implementation of the national projects focusing on the development of small business in Russia. As information resources centers, libraries can be a part of the support infrastructure for small and medium-sized entrepreneurship, providing business with information. For this purpose, libraries gained significant experience in the period of the Russian economic reform in the late 1980s and the 1990s. They were the first organizations to focus on the problem of information support for business. The proof of this is a flow of publications that can be divided into four areas of research: the information needs of businessmen; the opening and development of business and legal information centers in libraries; the adaptation of the Russian experience on information support of innovative activities to modern goals of high-tech economics; and the improvement of professional competencies of library and information science specialists in the field of business and entrepreneurship. The analysis of internet resources shows examples of libraries’ participation in information support of small businesses. It is noted that to join the infrastructure of small and medium-sized entrepreneurship, libraries should promote their information services through the “My Business” Centers that have been opened across the country.